TINGKAT INTELLIGENCE QUOTIENT (IQ) DAN CAPAIAN HAFALAN AL-QUR’AN SISWA DI YOGYAKART - Himmatin Nur Fadila (PSIKOWIPA (Psikologi Wijaya Putra), 2021)
The background of the problem studied in this study is the similarity between Intelligence Quotinet (IQ), memorizing the Qur'an and learning mathematics outcomes. IQ is characterized by rational, analytical, linear, absorbing mathematical concepts, systematic, logical order. Memorizing the Qur'an refers to the ability to systematically use concepts. Mathematics learning outcomes refer to the ability to think logically, analyze, critically, communicate and reason. The purpose of this study was to determine the relationship between Intelligence Quotinet (IQ) and Al-Qur'an Memorizing Achievement on Mathematics learning outcomes for fourth grade students of MI Wahid Hasyim. The type of research used is quantitative. The variables of this study consisted of independent variables and dependent variables. The independent variables are Intelligence Quotinet (IQ) and Al-Qur'an Memorizing Achievements, while the dependent variable is the fourth grade students' mathematics learning outcomes. The research population is students at MI Wahid Hasyim. The research sample is all fourth grade students. Research instruments include observations, interviews with teachers and student worksheets. The data analysis technique in this study used multiple regression test with the help of SPSS 23 software and Microsoft Exel.The results of the study prove that there is a relationship between Intelligence Quotinet (IQ) and Al-Qur'an Memorizing Achievement on mathematics learning outcomes. T-test Independent Samples Test N-gain that has been done obtained data that Sig. is 0.00 less than <0.05 and the average value of N-gain class 0.04 is in the medium category. So it can be concluded that there is a significant relationship between Intelligence Quotinet (IQ) and the achievement of memorizing the Qur'an on mathematics learning outcomes.